THE EFFECT OF FREE CASH FLOW, DEBT POLICY AND PROFITABILITY ON DIVIDEND POLICY - Sri Mulyati; Sopyan Yahya (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2022)
The purpose of this research is to find the effects of free cash flow, leverage, and profitability on dividend policy. This research uses a sample of 18 LQ 45 companies registered in BEI 2019-2020. The method used is purposive sampling. Hypothesis testing in this research uses multiple linear regression analysis. The result of this research shows free cash flow significantly affects the dividend policy. While leverage and profitability have no effect on dividend policy.